PERANCANGAN ARSITEKTUR INTERIOR RESTORAN MALIOBORO DENGAN MENGADOPSI ELEMEN BUDAYA TRADISIONAL OLEH BINA RUPA STUDIO - Jakelin, Chesy; Istanto, Freddy Handoko; Susan, M Y (Aksen : Journal of Design and Creative Industry, 2020)
Malioboro Restaurant was established in 2007 so after 12 years asking for a new face asking for the history of the establishment of a restaurant that was first built in Bali with the atmosphere and cultural distinctiveness created in Bali so that consumers in Surabaya can also find out the history of Malioboro Chicken Bone this is expected from Bali and is a special feature for soft bone chicken lovers in Surabaya. It is a problem determined by the site that is monotonous and does not reflect Bali in its design. Layout and circulation of visitors is irregular because of the placement of undirected space. There are also those who want to be written, will interpret the value of the company, namely feel the art by heart. The concept of the restaurant also wants to be introduced to the local culture in every room that is designed “contemporary”. Using traditional elements that give rise to the impression of a modern contemporary that prioritizes the principle of unity and harmony where elements are considered as elements and all elements that are interrelated and sustainable.